Possible ENSO Influences on the Northwestern Tibetan Plateau Revealed by Annually Resolved Ice Core Records. Issue 8 (19th April 2018) - Yang, Xiaoxin; Yao, Tandong; Deji,; Zhao, Huabiao; Xu, Baiqing
Abstract: Two annually resolved ice core records, one drilled on Mutztagata (7, 000 m above sea level) on the western slope (dated 1952–2002) and the other drilled on Kuokuosele (5, 600 m above sea level) on the southwestern slope (dated 1900–2010) of the Pamir Plateau of the northwestern Tibetan Plateau (TP), were selected to study possible El Niño–Southern Oscillation (ENSO) influences on the northwestern TP. δ 18 O at KKSL was more enriched, though both records varied in phase. Eight of the 10 noticeably strong El Niño events since 1955 corresponded to δ 18 O depletions in both ice core records, which were followed by δ 18 O enrichment. Atmospheric circulation indices, including water vapor flux and divergence, had a coincidence of a positive Indian Ocean Dipole mode with El Niño events, which contributed to the northward transport of southerly flows from the western Indian Ocean; its convergence with midlatitude wind flows at high levels depleted δ 18 O levels. The meridional shift in the Asian‐Pacific subtropical high induced by latent heat release due to precipitation in the northwestern Pacific was found to play an important role in initiating convergence. A statistical analysis confirmed the significant correlations in δ 18 O with the ENSO index and tropical and subtropical summer monsoon circulations. We noted that the dominant circulation pattern over the northwestern TP was characterized by a midlatitude flow regime that had a teleconnection with tropical sea surface temperatures. Therefore, ENSO is one of a variety of influences on ice core δ 18 O on the TP. Key Points: ENSO is one factor among many that affect ice core delta 18 O over the northwestern TP, with El Nino corresponding to low values Ice core d‐excesses from the northwestern TP suggest moisture source in the Mediterranean The midlatitude westerly flows, dominant over the northwestern TP, bridge the tropical Ocean with the circulation over the region